Triplex molecular beacons for sensitive recognition of melamine based on abasic-site-containing DNA and fluorescent silver nanoclusters1. Issue 37 (7th May 2015) - Wang, Ya; Sun, Qianqian; Zhu, Linling; Zhang, Junying; Wang, Fengyang; Lu, Linlin; Yu, Haijun; Xu, Zhiai; Zhang, Wen
<x xml:space="preserve">Abstract</x> A label-free and turn-on strategy based on a triplex molecular beacon for fluorescence melamine recognition with the signaling of Ag NCs was developed.